Urban co-living: housing option for young generation - Tiong, Siow Yin (2024)
Young generation in this century encounter many difficulties in homeownership. Despise government as a policy maker has put in many afford to ease the homeownership. In Malaysia, the planning system is impacted by housing providers as the housing market adapts to satisfy the demands of buyers. The basic housing needs are very much related to home preferences by young generation and these criteria are the focus of this study. The objective of this research paper is to understand current young generation accommodation option. By knowing respondents better thru their age group, gender and income level, the analysis of accommodation criteria, facilities and services element will be more certain. Criteria included location and housing attributes which will determine their way of choosing their housing option. Quantitative survey was employed for this research paper. AHP method has ease the study by using pairwise and comparison matrix are able to make the data analysis is fast manner. The information supplied gives a true picture of the views of the younger generation with respect to home preferences. The research revealed that these people's present living conditions have a big impact on the homes they choose in the future. For example, compared to those who rent, people who live with family members typically have less of an urgent need to enter into home ownership option. The younger generation emphasizes the importance of facilities and services, emphasizing their need for active participation. Numerous respondents expressed that security and safety are their top concerns. All the significance of these considerations are important in order for them to make the decision. Due to the high rate of car ownership in Malaysia and the common preference for shorter commutes over the availability of vehicles, accessibility, connectivity, and proximity to the place of employment are also given top priority.